2009
DOI: 10.1017/s0022029909990215
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of monensin and flaxseed hulls on ruminal and milk concentration of the mammalian lignan enterolactone in late-lactating dairy cows

Abstract: Four ruminally fistulated multiparous Holstein cows were assigned to a 4x4 Latin square design with a 2x2 factorial arrangement of treatments to study the effects of dietary supplementation of monensin and flaxseed hulls on ruminal and milk concentration of the mammalian lignan enterolactone (EL) and ruminal and faecal activity of beta-glucuronidase. The hypothesis was that monensin supplementation has no effect on the incorporation of EL into milk when cows are fed flaxseed hulls. Treatments were: 1) control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 39 publications
5
22
0
Order By: Relevance
“…That view is supported by other reports, e.g. Petit et al (2009). Similar observations were reported by Altenhofer et al 2014 (reduction in milk fat percentage, no effect on milk protein yield).…”
Section: Discussionsupporting
confidence: 90%
“…That view is supported by other reports, e.g. Petit et al (2009). Similar observations were reported by Altenhofer et al 2014 (reduction in milk fat percentage, no effect on milk protein yield).…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have shown that the phenolic compounds found in milk may originate from dietary plant material . When cattle are fed high levels of particular crops, some specific phenolics may be detected in the milk, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…genistein, equol and daidzein, all derived from clover . Similarly, flaxseed meal is a feed ingredient which can enhance the concentration of mammalian lignan enterolactone in milk . Thus, despite the ruminal biotransformation of dietary phenolic compounds, those present in milk are likely to be incorporated directly from the diet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flaxseed hulls contain 29•4% ether extract and most of it is digested in the rumen as shown by higher digestibility of ether extract when hulls are administered in the rumen than when they are administered in the abomasum (Kazama et al 2010). However, although flaxseed hulls are a rich source of n À 3 FA (Petit et al 2009), there is no information on the effect of flaxseed hull supplementation on digestibility of fatty acids.…”
mentioning
confidence: 99%